Comparative diurnal and seasonal variations of ACTH, cortisol and aldosterone in Ouled Djellal and D’Man sheep breeds reared in arid lands (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Amokrane-Ferrah A, Annane A, Ferrouk-Boukenaoui N, Khaldoun M, Amirat Z, Mormede P, Khammar F. 2021. Comparative diurnal and seasonal variations of ACTH, cortisol and aldosterone in Ouled Djellal and D’Man sheep breeds reared in arid lands. Biodiversitas 23: 388-395. This study aimed to explore the diurnal and seasonal variations of adrenocorticotropic hormone (ACTH), cortisol and aldosterone, main hormones involved in adaptation to the harsh climate of the Sahara Desert in two breeds of sheep (Ovis aries Linnaeus, 1758), Ouled Djellal rams (seasonal breeder) and D'Man (no seasonal breeder). Blood samples were taken every hour for 24 hours during equinoxes and solstices. Plasma ACTH levels were similar in the two breeds, with higher levels in the morning and a seasonal rhythm characterized by lower levels and dampened diurnal cycle in winter. In most experimental conditions, plasma cortisol levels showed no circadian rhythm but marked ultradian variations. The seasonal cortisol rhythm was different from the ACTH rhythm and characterized by lowest levels at equinoxes and highest levels in summer. Mean cortisol levels were higher in Ouled Djellal than in the D’Man breed, which may favor better robustness of Ouled Djellal sheep. Plasma aldosterone levels were characterized by diurnal variations with an acrophase around midnight, with large differences across breeds and seasons. In contrast to cortisol, the seasonal rhythm of plasma aldosterone showed the highest levels at equinoxes and lowest at solstices. These changes can be driven by environmental conditions and exceptionally high summer temperatures.
Keywords: Biological rhythm; hypothalamic-pituitary-adrenocortical axis; stress; robustness; Sahara Desert